Austria under the auspices of global agritourism values: a narrative literature review - Quendler, Erika; Embacher, Hans; Magnini, Vincent; Plaikner, Alexander; Stotten, Rike (Frontiers in Sustainable Tourism, 2024)
The concept of agritourism has been studied in various transnational, national, and regional or local contexts. Its growing popularity raises questions about common definitions and their variations. With this in mind, the Global Agritourism Network Committee's Definitions and Standards elaborated a series of core global values. This review examines the situation in Austria based on these values, such as synergistic potential, agricultural diversity, the integration within agriculture and its derivatives, resource showcasing, and authentic experiences. The objective is to investigate the prevalence of these global core values within the Austrian situation. Consequently, this review aims to contribute to a broader understanding by identifying similarities and potential gaps between these global core values and local practices. Additionally, the review considers how enhancing global transparency could improve national agritourism practices. The review draws on a number of Austrian reference sources, namely accommodation statistics, the farm structure survey, and guidelines from the “Holidays on the Farm” association, as well as relevant literature from 2006 to 2024. Databases like Scopus and Web of Science were searched using keywords such as “agritourism,” “farm holiday,” and “Austria.” A total of 27 “publications” in English and German were analyzed with MAXQDA. The findings indicate that Austria is a unique case study, able to contribute to global discussions but also needing to preserve local identity. The review confirms that the Austrian situation adheres to the global core values but is also shaped by national guidelines, particularly by those set by the “Holidays on the Farm” association. These guidelines, serving as a role model, emphasize quality, marketing, and cross-sector collaboration. The review also highlights the importance of juxtaposing the global perspective with the local realities. Given the theoretical overlay of the global core values, further research should explore their application in other countries and regions. Mixed-methods approaches could offer deeper insights on their suitability globally. Developing robust assessment tools would help evaluate these values across different national contexts, providing useful guidance for policymakers and practitioners.